Pengaruh Pupuk NPK dan Guano Terhadap Pertumbuhan dan Produksi Tanaman Terung (Solanum melongena L.) - Charis Suganda; Amrul khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
The development of eggplant (Solanum melongena L.) cultivation is the fastest in Southeast Asia, one of which is in Indonesia. This study aims to determine the interaction effect of NPK fertilizer and guano fertilizer on eggplant growth and production and to determine the effect of NPK fertilizer and guano fertilizer as a single factor on eggplant plant growth and to obtain the best dose. This research has been carried out at the Experimental Garden, Faculty of Agriculture, Riau University, Bina Widya Campus KM 12.5, Pekanbaru. The research lasted for 4 months, starting from July 2021 to November 2021. The materials used in this study were round eggplant seeds of Pondoh variety, guano fertilizer, NPK fertilizer, Dithane M-45, Furadan 3G, Decis 25 EC, rope rapia, wood and nails. The tools used in this study were hoes, machetes, knives, scissors, rakes, polybags, scales, meter, paranet, gembor, hammer, plastic, camera, and stationery. This study used a factorial completely randomized design (CRD). consists of 2 factors. The first factor is the treatment of NPK fertilizer (16:16:16) (N) which consists of 4 levels, namely: N0 = Control (without NPK fertilizer), N1 = NPK fertilizer 100 kg.ha-1, N2 = 200 kg NPK fertilizer .ha-1 and N3 = NPK fertilizer 300 kg.ha-1 The second factor is the treatment of guano fertilizer (G) which consists of 4 levels as follows: G0 = control (without Guano fertilizer), G1 = 10 tons of guano fertilizer. ha-1 , G2= guano fertilizer 15 tons.ha-1 and G3= guano fertilizer 20 tons.ha-1. From these two factors, 16 treatment combinations were obtained. Each treatment consisted of 3 replications so that the number of experimental units obtained was 48 units. Each unit consists of 4 plants, 2 of which are used as samples, the total number of plants is 192 plants. Based on research that has been carried out to get good growth and production of eggplant plants can use NPK fertilizer at a dose of 300 kg.ha-1, but to get better results can use guano fertilizer 15 tons.ha-1 and NPK fertilizer 300 kg. ha-1. Keywords: eggplant, NPK, Guano Fertilizer